Strengthening of Unreinforced Masonry with Fibre Reinforced Concrete - Gayathri, S; Kanchidurai, S; A. Krishanan, P; Baskar, K (International Journal of Engineering and Technology, 2018)
Unreinforced Masonry buildings are vulnerable because the walls and parapets aren’t securely tried to the floors and roof. In an earthquake, parapets can break away, walls pull apart and the floors collapse. This paper presents the experimental study performed on the flexural bond strength of unreinforced brick masonry prism. Different percentage (1%, 2%, and 3%) of Hooked Steel Fibre was used. One of the most geometrical parameters of fibres is their length, diameter and aspect ratio. Masonry prism will be cast and tested as per the guidelines are given in ASTM E518/E518-15. The results of the flexural bond strength test of prisms with and without fibre discussed.